The Impact of Window-Shopping Strategy towards Students’ Score on Topic of Linear Equations of Two Variables - Hesti Filmiari; Ramadoni; Dewi Yuliana Fitri (Rangkiang Mathematics Journal, 2023)
This research is motivated by the low scores of students in learning mathematics. The purpose of this study was to determine the effect of applying the window shopping learning model to the learning outcomes of class VIII students of SMP Negeri 29 Sijunjung. This type of research is experimental research with a quantitative approach. As a result, the class with the window shopping learning model has an average of 61.14 and the class with the conventional learning model has an average of 43.04. The results of testing the hypothesis obtained tcount = 2.3569 and ttable = 1.7056, where tcount > ttable, so the hypothesis is accepted. It can be concluded that the application of the window shopping learning model affects the learning outcomes of Class VIII students of SMP Negeri 29 Sijunjung.